Jawabanmu

2014-05-15T22:44:20+07:00
F(x) dibagi (x-1) sisa 5

f(x) dibagi x²-2x-3 sisa (2x + 1) atau f(x) dibagi (x-3)(x+1) sisa (2x+1)
f(-1) = 2(-1) + 1 = -2 + 1 = -1

f(x) dibagi x² - 1 atau f(x) dibagi (x-1)(x+!)

                       f(x) ⇒ ax + b = sisa
untuk (x-1) ⇒ f(1)  ⇒  a + b = 5
untuk (x+1) ⇒f(-1) ⇒ -a + b = -1 +
                                       2b = 4
                                         b = 2
a + b = 5 ⇒ a + 2 = 5 ⇒ a = 3
f(x) = ax + b ⇒ f(x) = 3x + 2

Jadi. jika f(x) dibagi x² - 1 sisanya 3x + 2